Take the Law into Your Own Hands: Modernist and Detective Fiction in William Faulkner’s Intruder in the Dust and Light in August - Li-Hsion Amanda Liu, (Miscelánea: A Journal of English and American Studies, 2016)
William Faulkner’s Intruder in the Dust and Light in August are not conventionally associated with genres of crime and detection. Nevertheless they include multiple homicides, false accusations, ethnic conflicts, feeble enforcement of the law, and a nearly total failure to carry out impartial justice, within a narrative setting. Just as an ongoing controversy swirls around the topic of how to ensure justice is meted out on the basis of equity, so unbridgeable racial disparities have adversely impacted the legal proceedings in court. In order to examine the complex interconnections between race and law, this paper reflects a modernist approach to Faulkner’s works by revealing the similarities between modernism and crime writing.